Dejavnost čmrljev preko dneva in sezone - Bevk, Danilo (Acta entomologica slovenica (Ljubljana), 2007)
Observations of activity of three bumblebee species (Bombus pascuorum, B. humilis and B. lapidarius) during the day and season are presented. The frequency of outflights was used as the criterion of activity. The observed species are distinguished by the pattern of changes in frequency of outflightsduring the season as well as over the day. The differences in frequencies of outflights during the day were significant at the beginning of observations in July but diminished later in the season. B. lapidarius was thefirst to reach peak of activity during season, followed by B. humilis and B. pascuorum. Differences between species can be interpreted as a mechanism ofreduction of interspecific competition. They should be taken into account atquantitative samplings of these insects.
Keywords: čmrlji; entomologija; kompeticija